(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
"Matru Devo Bhav" and "Pitru Devo Bhav" are the Sanskrit phrases, which reflects the sentiments to one’s parents. Traditionally it was seen that elderly people were given love and respect but now in the 21st-century world, the transformation of joint family to the nuclear family had created a huge effect on their social lives which has caused emotional abuse, physical problems, financial insecurity, lack of social security and social isolation. India, like many other countries, is heading towards the phenomenon of population aging. Improved health care facilities, awareness, and spread of life-saving drugs coupled with socioeconomic progress have resulted in increase in the number of aged people. The Indian aged population which is currently the second largest in the world has raised from 942.2 million in 1994 to 1.36 billion in 2019. The rising population of aged has become challenging for the government to face the issues and problems of it. The Government of India has taken various legal steps in order to narrow down the effects of consequences through Acts, policies, schemes and programs but still there is a large number of older people whom these services were not reached or available. It is because most of the elder people didn’t know about it. Some of them working in the public sector, will get pension on a regular basis but there are a huge number of older people working in the unorganized sector where there is no such provision for pension. So, the Indian government should lay more emphasis on the concept of “Pension for All”.